Transição sustentável das compras públicas de alimentos: o caso dos restaurantes das universidades federais no estado do Paraná - Giombelli, Giovana Paludo (2018)
The concern with sustainable development is a sign that the current agrifood model is being questioned for its economic, social and environmental consequences. It is the recognition that natural resources are limited and that development must be on the way to social justice. It opens like this space for the discussion of propositions of a transition to a sustainable model that involves the establishment of forms of organization that facilitate the intensification and collaboration between consumption and production and that meets the needs of the present without compromising the ability of future generations to meet their needs. Among the food policies created with this new perspective is the PAA. In your modality of Institutional Purchase (CI), together with Decree nº 8.473/2015 of June 22, 2015, provides that public institutions with regular demands for foodstuffs use at least 30% of their resources to purchase products directly from family farmers and cooperatives without the need for a public call. Thus, this study aimed to analyze the early years of deployment and implementation of this modality in the restaurants of the Federal University of Paraná (UFPR, UFFS, UTFPR, UNILA), identifying the mechanisms built and any difficulties that each institution had to deploy or not the decree, as well as identifying important actors in this process. The Multilevel Perspective and the Actor-Oriented Perspective were used. The methodology used was a case study with quantitative and qualitative emphasis. The information was collected through an online questionnaire (22 UK managers and technical managers) and semi-structured interviews (eight UK managers, four managers from outsourced companies and seven individual or co-operative farmers). Descriptive analyzes were used for quantitative data and content analysis for qualitative data. Of the 24 Campi, only the Campus of the UTFPR - Santa Helena and UNILA, did not participate of the research, because they do not possess RU. Of the 22 investigated four campuses they buy from agriculture. None of the three institutions managed to reach the proposed 30%. UFPR reached close to 20%, and later there were problems that made it no longer acquire AF products. The UFFS and UTFPR reached 2% of their purchases. The role of the actors was fundamental so that the development of this proposal of purchase of the AF could happen, but in none of the cases was enough for that the same one continued. The reported difficulties were the internal bureaucracy of universities, outsourcing of the UK, lack of understanding of the policy on the part of managers, lack of social mobilization, councils such as Consea and the like. This can also, to a certain extent, reduce pressure for changes at all three levels - niche, regime and landscape. That is, as there are no actors at the local level pressing for change, there are no changes in the regime either. On the other hand, intact paradigms such as the non-questioning of development processes that go from one strictly economic to another inclusive and sustainable do not affect hegemonic regimes.